-6+8b=10+10b

Simple and best practice solution for -6+8b=10+10b equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6+8b=10+10b equation:



-6+8b=10+10b
We move all terms to the left:
-6+8b-(10+10b)=0
We add all the numbers together, and all the variables
8b-(10b+10)-6=0
We get rid of parentheses
8b-10b-10-6=0
We add all the numbers together, and all the variables
-2b-16=0
We move all terms containing b to the left, all other terms to the right
-2b=16
b=16/-2
b=-8

See similar equations:

| (3w-1)(9-w)=0 | | 4^2x=8^x=4 | | -7-5z=-5z-7 | | 2(x+1)+3(x+2)=x+16 | | 3a=(a+7)+87 | | -6x+8=-3×-10 | | X/5x0.5=0.8 | | 10=(12–2k) | | 11x-9×=18 | | 7x+42+5x-6=180 | | 1=6x-4-5x-15 | | --8u=-8-8u | | 7a+a=42 | | 8/3-3=x/9+3 | | 0=-16t2+20t | | -2-9u=-9u | | 5x–6=14 | | 1.7y–8=2.7y+4 | | 1/8(4w+8)=-4(w+2) | | 3x-52=31 | | 3x−4=−0.5x+3 | | -10-4j=2-6j | | m/8–4=-2 | | 3+2(2x—5)=5x-4 | | (8-u)(4u+2)=0 | | 10(x-8)=6(x+8) | | o/5+4=2 | | 3x^2−48=0 | | 3x−4=−12x+3 | | -6d-4=-4-6d | | 3x2−48=0 | | 8=p/7= |

Equations solver categories